Impact of Government Health Expenditure on Maternal and Child Mortality Rates in a CLMV Country - SIPASEUTH, Khamnikone; SOUKSONE, Thatniyom; CHANCHSAMONE, Addy (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The health of the citizens is a concern for all levels of government, as well as for CLMV countries, which first prioritized a portion of health expenditure in the health sector to reduce maternal and child mortality rates, particularly in rural areas. In order to analyze the data using fixed effect regression and random effect regression, we used balanced panel data to examine the impact of government health expenditure on maternal and child under-five mortality rates in a CLMV country. As a result of this study, increased government health expenditure had a significant impact on reducing the maternal mortality rate while having no effect on the child mortality rate. Furthermore, there are additional independent variables that affect the maternal and child under-5 mortality rates in a CLMV country, such as GDP per capita, which has a significant impact on reducing the child mortality rate but no impact on reducing the maternal mortality rate. Nevertheless, women's primary school enrollment and use of basic water service rates were statistically significant in CLMV countries.